Partial Intravenous Anesthesia and epidural block for correction of Portosystemic Shunt in canine: Case report - Priori, Déborah Belmonte; Rutzen , Cássia Thaís; Lee, Dayanne Helen Lima de Araujo da Conceição; Tolotti, Fátima Luisa; Mombach, Veronica; Gorczak, Rochelle (Seven Editora, 2023)
The Portosystemic Shunt is a vascular alteration that causes the diversion of blood flow from the liver to the systemic circulation, preventing the hepatic filtration of substances. The treatment of this deviation is surgical, therefore, in the anesthetic procedure, it is important to choose the drugs, avoiding those that go through the liver biotransformation process. The purpose of this report is to describe the use of partial intravenous anesthesia (PIVA) and epidural block in a case of repair of Portosystemic Shunt in a canine. Yorkshire, 1 year old, not spayed, weighing 2 kg, with congenital and extra-hepatic deviation. After MPA and with the animal induced, an epidural block was performed using lidocaine without vasoconstrictor and morphine. For maintenance, PIVA was performed with continuous infusion of remifentanil and lidocaine, offering good intraoperative analgesia, associated with local anesthesia, and reducing the need for the use of inhalational agents. During surgery, the patient had hypotension as the only complication, being related to the use of drugs that potentiated hypotension, such as acepromazine and morphine, but the patient was responsive to the load test with ringer lactate associated with ephedrine, to stabilize the condition and had a fast return anesthetic without painful stimulus, demonstrating that the association of the PIVA technique and the block was effective in the analgesia of the patient in question. DOI:https://doi.org/10.56238/globalhealthprespesc-053